Comparison of HbA1c and OGTT for the diagnosis of type 2 diabetes in children at risk of diabetes - Min Sun Kim; Dae Sun Jo; Dae-Yeol Lee (Elsevier, 2019)
Background: The aim of this study was to evaluate the correlation between plasma glucose and HbA1c and the diagnostic accuracy of HbA1c as a screening tool to identify asymptomatic diabetes mellitus in children and adolescents with obesity or asymptomatic glucosuria. Methods: A total of 190 subjects who underwent an oral glucose tolerance test (OGTT) to confirm diabetes were categorized into normal glucose tolerance (NGT; n = 117), impaired glucose tolerance (IGT; n = 33), and diabetes (DM; n = 40) according to the OGTT. Forty-seven patients with DM were diagnosed by either OGTT or HbA1c levels. The diagnostic accuracy for the detection of diabetes is based on 47 patients. Laboratory tests were performed after 12 h of fasting. Results: According to the HbA1c criterion, 107 (55.3%) subjects were in the NGT group, 41 (21.6%) were in the IGT group, and 42 (22.1%) were in the DM group. Diagnostic sensitivities of HbA1c and 2-hour plasma glucose level following OGTT (2-h OGTT) for DM were significantly higher than that of fasting plasma glucose, FPG (89.4, 85.1 vs. 63.8%). In addition, the area under the curves of diagnostic criteria was 0.970 for HbA1c, 0.939 for FPG and 0.977 for 2-h OGTT. Mean FPG and 2-h OGTT for HbA1c level >6.5% were 115.2 mg/dL and 181.8 mg/dL, respectively. The optimal HbA1c level cut-off point for predicting DM is 6.15%, with a sensitivity of 95.7% in Korean children and adolescents. Conclusion: The HbA1c criterion ≥6.5% was adequate to detect DM among Korean children and adolescents with obesity or asymptomatic glucosuria. We also recommend HbA1c level of 6.15% as the optimal cut-off point for detecting DM in Korean children and adolescents. Keywords: Diabetes mellitus, HbA1c, Oral glucose tolerance test, Obesity, Glucosuria